How clinicians experience a simulated antiretroviral therapy adherence exercise: A qualitative study - Justin G. Engelbrecht; Fidele K. Mukinda; Beryl Green; Donald Skinner (African Journal of Primary Health Care & Family Medicine, 2018)
Background: With the shift of paediatric antiretroviral therapy (ART) from tertiary to primary health care, there has been a need to train clinicians working in primary health care facilities to support adherence to treatment. An adherence simulation exercise was included in a course on paediatric human immunodeficiency virus (HIV) and tuberculosis (TB) to stimulate health care providers’ awareness and generate empathy of complex paediatric adherence practices.